1964
DOI: 10.1002/pol.1964.100021013
|View full text |Cite
|
Sign up to set email alerts
|

Endgroup studies in persulfate‐initiated vinyl polymer by dye techniques. Part I. Initiation by persulfate alone

Abstract: SynopsisQuantitative determination of endgroups of poly(methy1 methacrylate), polystyrene and poly(viny1 acetate) obtained by aqueous initiation with KzSzOs under varied. conditions have been made by the application of two sensitive dye techniques, called the dye partition technique and the dye interaction technique. The description of the dye techniques are given in detail. Sulfate (OSOS-) and hydroxyl (OH) endgroups are generally found to be incorporated in the polymers to an average total of 1.5 to 2.5 endg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1966
1966
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…Again, the end group analysis 19 of the free homopolymer (PMMA) from the gross products gave a positive response for sulphate and hydroxyl end groups, which confirms the presence of sulphate ion radical (SO 4 Ϫ • ) and hydroxyl radicals ( • OH) as primary radicals in this system. Taking all of the above into consideration, the probable mechanism may be described as follows.…”
Section: Mechanismsupporting
confidence: 58%
“…Again, the end group analysis 19 of the free homopolymer (PMMA) from the gross products gave a positive response for sulphate and hydroxyl end groups, which confirms the presence of sulphate ion radical (SO 4 Ϫ • ) and hydroxyl radicals ( • OH) as primary radicals in this system. Taking all of the above into consideration, the probable mechanism may be described as follows.…”
Section: Mechanismsupporting
confidence: 58%
“…This is because of the possibility that the initiator or end group may undergo a chemical reaction that will produce an end group that is a different chemical species entirely and may or may not be charged. For instance, one such reaction that is commonly known to occur with the sulfato radical produced from persulfate initiator is the hydrolysis reaction with water to produce a hydroxyl radical32 (the solid bullet • symbol denotes a radical species). This hydroxyl radical may then initiate polymerization in the water phase forming an hydroxyl end group on the polymer chain.…”
Section: Introductionmentioning
confidence: 99%
“…Palit et al reported the presence of sulfate groups in polystyrene (PS) and PMMA prepared by persulfate initiator using the dye partition method [16][17][18][19][20]. The persulfate-initiated polymers contain very low amounts of sulfate end groups, about 0.05 -0.3 per polymer molecule for PS and 0.6 -0.7 for PMMA [18].…”
Section: Resultsmentioning
confidence: 99%